PS-049 Prospective detection of adverse drug reactions among 2263 hospitalised children over a 19 month period: Eremi intermediate report. (14th February 2016) - Lajoinie, A; Nguyen, KA; Mimouni, Y; Paret, N; Carcel, C; Malik, S; Milliat-Guittard, L; Dode, X; Vial, T; Kassai, B
Abstract : Background: Off-label and unlicensed (OLUL) drug use is a dominant practice in children. Recent observational studies suggest that OLUL drugs are more likely to be responsible for adverse drug reactions (ADRs) in children than licensed medicines (Santos 2008; ADRIC 2014). Purpose: EREMI study prospectively assessed the relationship between OLUL drug use in children (0–15 years, ≥3 hospital days) and ADR occurrence. This intermediate report describes ADRs detected over 19 months (September 2013 to January 2015) in our children's hospital. Material and methods: ADRs were detected by the EREMI team (physicians/pharmacists) analysing patient medical records, drug administrations, physiological parameters and biological outcomes using the hospital information system, prior to validating suspected ADRs with the clinical team. Results: 2263 children were hospitalised during the study period (3122 hospital stays, 20 571 drug prescriptions). 263 ADRs occurred in 183 children: 1/12 of hospitalised child experienced at least 1 ADR and 1/80 prescriptions was associated with an ADR. Among the detected ADRs, 117/263 ADRs (44%) were responsible for prolongation of hospitalisation (eg, pancreatitis/valproate) and 32/263 (12%) were severe or life threatening (eg, hypokalaemia). Frequency of ADRs in the 7 participating wards is detailed in table 1 . The most frequent ADRs were hypokalaemia (n = 27), withdrawal syndrome (n = 19), sleepiness (n = 16), cytolysis/cholestasis (n = 16), hypotension (n = 15) and skin reactions (n = 14). Conclusion: As expected, a great ADR incidence was found for the resuscitation ward. However, the frequent occurrence of ADRs using psychiatric drugs in children was unanticipated. The analysis of detected ADRs revealed that the majority were preventable: systematic warning of clinical staff for ADR risks would help in preventing ADRs. References and/or Acknowledgements: ANSM funding; EREMI group. No conflict of interest.